Modeling and Up-Gradation of Concentric Circular Shaped Patch Antenna to Array Antenna with the Improved Performance for 5G Millimeter- Wave Communication - Azeem Mirani; Sanjha Rehman Memon; Mumtaz Qabulio; Qazi Ijaz; Imran Khan Jatoi (Pakistan Journal of Engineering Technology & Science)
This work is primarily devoted to design and aim at high gain of 8×8 array starting from 2×2, 4×4, 8×8 patch array microstrip antennas by upgrading circular shaped antenna to array antenna. It finds applications for utilizing 28 GHz as a licensed bandwidth, such as in wireless communication networks, satellite communications, radar systems, global positioning systems and telemedicine applications. The antenna exhibits a significantly high gain, remarkable directivity, and achieves a peak gain of 15.1 dB for both the E and H planes. It operates independently for horizontal and vertical polarizations. The design uses Rogers RT/Duroid as the substrate, featuring a square shape with a thickness of 0.787 mm and side dimensions of 20 mm. The total size of the antenna is 20 × 20 × 0.787 mm³. It is tuned to resonate at 28 GHz, achieving a return loss of -24.69 dB and offering an impedance bandwidth of 29%. The enhanced performance of this antenna is evident in terms of its return loss, peak gain, radiation pattern, impedance matching, bandwidth, and directivity, making it a promising solution for 28 GHz mm-wave communication systems. Fifth generation (5G) antennas. This problem can be solved by using high gain antenna. Therefore, the antenna structure is designed and simulated using HFSS ANSYS EDT 2021 / R2 Microwave Studio.